Outage Performance Based on Optimal Relay Location in Multi-node Relay Network - Yaolian Song; Yubin Shao; Hua Long; Xuanhui Xi (Institute of Advanced Engineering and Science, 2013)
In this paper, we investigate the outage performance of multi-node relay network under equal power allocation (EPA) scheme. Due to the mobility of relay nodes, we proposed to design a method that considers random relay location based on random model. We conduct deep experiments which demonstrate that there exists optimal relay location to minimize the outage probability of multi-node relay networks. Finally, simulation results show that the outage performance of the multi-node relay network is closely related to the relay location. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.2742